2018
DOI: 10.3233/cbm-170471
|View full text |Cite
|
Sign up to set email alerts
|

LINC00261 suppresses cell proliferation, invasion and Notch signaling pathway in hepatocellular carcinoma

Abstract: These results indicated that LINC00261 may be a potential target of HCC treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 20 publications
6
45
0
Order By: Relevance
“…Although our data showed similar LINC00261 functions on cancer cell aggressiveness as reported previously, 15,[17][18][19]23 the molecular mechanisms are totally different. In colon cancer, LINC00261 downregulates Wnt signalling activity through restraining β-catenin from cytoplasm into nuclei and promoting β-catenin degradation.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Although our data showed similar LINC00261 functions on cancer cell aggressiveness as reported previously, 15,[17][18][19]23 the molecular mechanisms are totally different. In colon cancer, LINC00261 downregulates Wnt signalling activity through restraining β-catenin from cytoplasm into nuclei and promoting β-catenin degradation.…”
Section: Discussionsupporting
confidence: 85%
“…Now, we first time reported that LINC00261 was also downregulated in endometrial carcinoma, and the LINC00261 levels were further decreased in endometrial carcinoma with lymphatic metastasis. Although our data showed similar LINC00261 functions on cancer cell aggressiveness as reported previously, the molecular mechanisms are totally different. In colon cancer, LINC00261 downregulates Wnt signalling activity through restraining β‐catenin from cytoplasm into nuclei and promoting β‐catenin degradation .…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Host genes may affect small nucleolar RNAs (snoRNAs) expression through co-transcriptional regulation [44]; snoRNAs are non-coding RNAs of 60-300 nucleotides in length [45]. Up-regulated LINC00261 has also been reported to suppress the proliferation and invasion of HCC cells [46]. These basic findings may, in part, hint that snoRNA host genes may have a profound impact on the prognosis of HCC, emphasizing that the prognostic value of lncRNAs warrants future research.…”
mentioning
confidence: 99%